Analysis of annual program planning for improving Islamic value-based learning quality in senior high schools - Amelia Dewanti; Abd. Madjid (UIN Salatiga, 2026)
This study analyzes annual program planning (Program Tahunan/Prota) in improving the quality of Islamic value-based learning in Islamic Religious Education at SMA N 1 Karangmojo. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation, then analyzed with the Miles and Huberman interactive model involving data condensation, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings reveal that the annual program is designed based on Learning Outcomes (Capaian Pembelajaran/CP), students' needs and characteristics, and the vision and mission of Islamic Religious Education. The program emphasizes strengthening faith, Qur'anic values, morality, fiqh, and Islamic history integrated into both classroom instruction and school culture. Prota serves as a key guideline for teachers in organizing learning strategies, time allocation, and evaluations in a systematic and sustainable manner. The study also highlights that collaboration among teachers, schools, and parents contributes significantly to successful implementation. Overall, Islamic value-based annual planning provides a strategic framework for developing adaptive, systematic, and character-oriented learning within the Independent Curriculum.